2008
DOI: 10.1080/15226510802096069
|View full text |Cite
|
Sign up to set email alerts
|

Contaminated Soil Phytoremediation byCyperus LaxusLam. Cytochrome P450 Erod-Activity Induced by Hydrocarbonsin Roots

Abstract: Laboratory and greenhouse experiments with Cyperus laxus Lam were conducted to determine the rate and extent of phytoremediation and the effect of hydrocarbons on the cytochrome P450 EROD (7-ethoxyresorufin-O-deethylase) enzymatic activity in roots. Plants were cultivated on hydrocarbon-contaminated soil (HCS) and spiked perlite. Phytoremediation was evaluated using 6.5 kg HCS (173 +/- 15 mg total petroleum hydrocarbons [TPH] g(-1) of dry soil) pots at different moisture contents; the average removal rate was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The slower and reduced degradation of TPH in uncontaminated soil can be attributed to its lack of plants. Lopez‐Martinez et al 25 also found significant reduction of TPH by Cyperus laxus Lam. over 24 months when plants were cultivated on hydrocarbon‐contaminated soil and spiked perlite.…”
Section: Resultsmentioning
confidence: 85%
“…The slower and reduced degradation of TPH in uncontaminated soil can be attributed to its lack of plants. Lopez‐Martinez et al 25 also found significant reduction of TPH by Cyperus laxus Lam. over 24 months when plants were cultivated on hydrocarbon‐contaminated soil and spiked perlite.…”
Section: Resultsmentioning
confidence: 85%
“…It has been suggested that root exudates which control the quality and quantity of microbial population in soil also alter plant metabolism during crude oil associated stress condition thereby promoting the degradation of hydrocarbons/oil in vegetated treatments 6 . Several studies have showed significant changes in TOG profiles in oil polluted soils after treatment by herbs/ grasses [22][23][24] . Nevertheless, reduction in TOG levels (17.36%) in the present study was found comparatively less as against the previous works which can be because of the time duration of the experiment (60 days), besides the high concentration levels of crude oil of the experimental soil.…”
Section: Discussionmentioning
confidence: 99%
“…Its common name is "Pelo de Chino", but in some states of the country like Veracruz, it is known as "Zacate Chontul" (López, 2013). It taxonomically belongs to the Tracheophytes division of the class Angiospermae and sub-classes Monocotyledonous, it is in the Family Cyperaceae, and belongs to the genus: Cyperus, species: Cyperus laxus lamouroux (López et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To date, studies and assessments related to C. laxus remain scarce, but there are other successful cases in which the Cyperus genus has been used (Escalante et al, 2005;López et al, 2008).…”
Section: Introductionmentioning
confidence: 99%